2017
DOI: 10.1007/s11746-016-2940-4
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Butter Substitute (CBS) Produced from Palm Mid‐fraction/Palm Kernel Oil/Palm Stearin for Confectionery Fillings

Abstract: crystal morphology and monotectic behaviors comparable to those of CB.Abstract This study investigated the physicochemical properties of ternary mixtures of palm mid-fraction (PMF):refined bleached deodorized palm kernel oil (RBDPKO):refined bleached deodorized palm stearin (RBDPS) for cocoa butter substitute (CBS). Fatty acid constituents, triacylglycerol constituents, solid fat contents (SFCs), melting behavior, polymorphism and crystal morphology were determined using gas chromatography (GC), high-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…Whereas IP presented a well-distributed, smooth and nearly round pattern, and ball-like crystal microstructure were formed. The morphology of IP was found to be consistent with that observed by Biswas et al (2017). Besides, after interesterification, crystal size was obviously decreased to less than 50 lm in diameter.…”
Section: Microstructuresupporting
confidence: 79%
“…Whereas IP presented a well-distributed, smooth and nearly round pattern, and ball-like crystal microstructure were formed. The morphology of IP was found to be consistent with that observed by Biswas et al (2017). Besides, after interesterification, crystal size was obviously decreased to less than 50 lm in diameter.…”
Section: Microstructuresupporting
confidence: 79%
“…SFC of BT, physical blends and IF differed slightly between 15 and 25 , which were 19.66, 18.71, and 17.66 , respectively, indicating that they have similar cooling effects. In particular, the temperature range in which SFC of IF significantly decreased shifted to 10-20 in the low temperature range from 42.84 to 23.73 , which may attributed to the saturated fatty acid composition in TAG i.e., the content of SSS decrease, SUS and SUU increase had changed 29,30 . It was demonstrated that what was referred to as the desirable plastic range of fats should have the properties that the SFC contains roughly 15-35 solids at 25 31 .…”
Section: Solid Fat Contentmentioning
confidence: 96%
“…Without enzymatic interesterification, it is difficult to obtain a CBE that resembles the TAG profile of CB. There are many studies that have produced CBS and cocoa butter improvers (CBI) that can increase hardness and the melting point of the CB blend (Biswas, Cheow, Tan, Kanagaratnam, & Siow, ; Maheshwari & Yella Reddy, ). However, CBS and CBI can only be added in a certain amount before altering the properties of the chocolate product.…”
Section: Introductionmentioning
confidence: 99%